2015
DOI: 10.1016/j.aim.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Hausdorff dimension estimates for restricted families of projections in R3

Abstract: This paper is concerned with restricted families of projections in R 3 . Let K ⊂ R 3 be a Borel set with Hausdorff dimension dim K = s > 1. If G is a smooth and sufficiently wellcurved one-dimensional family of two-dimensional subspaces, the main result states that there exists σ(s) > 1 such that dim π V (K) ≥ σ(s) for almost all V ∈ G. A similar result is obtained for some specific families of one-dimensional subspaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 13 publications
(27 reference statements)
2
27
0
Order By: Relevance
“…One of the problems treated in [4] is to say something about the dimension of π t (B) for generic t ∈ [0, 1]. Fässler and Orponen prove that (a) if α ≤ 1 then dim(π t (B)) = dim (B) for almost all t ∈ [0, 1], and (b) if α > 1 then there exists σ = σ(α) > 1 such that the packing dimension of π t (B) exceeds σ for almost all t. In a subsequent paper, [6], Orponen considers the particular γ given by…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 96%
“…One of the problems treated in [4] is to say something about the dimension of π t (B) for generic t ∈ [0, 1]. Fässler and Orponen prove that (a) if α ≤ 1 then dim(π t (B)) = dim (B) for almost all t ∈ [0, 1], and (b) if α > 1 then there exists σ = σ(α) > 1 such that the packing dimension of π t (B) exceeds σ for almost all t. In a subsequent paper, [6], Orponen considers the particular γ given by…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 96%
“…Orponen [71] also showed that there exist numbers σ(λ) > 1 defined for λ > 1, and increasing with λ, such that if dim H E > 1 then dim…”
Section: Projections In Restricted Directionsmentioning
confidence: 99%
“…Estimates for packing dimensions of projections may be found in [26]. The introduction of the paper [71] provides a recent overview of this area.…”
Section: Projections In Restricted Directionsmentioning
confidence: 99%
“…In [Orp3] Orponen was able to do this for the special family of orthogonal projections onto the lines l θ spanned by (cos θ, sin θ, 1) and their orthogonal complements. In [Orp3] Orponen was able to do this for the special family of orthogonal projections onto the lines l θ spanned by (cos θ, sin θ, 1) and their orthogonal complements.…”
Section: This Is Sharp By Trivial Examples; Consider Product Setsmentioning
confidence: 99%